Epiphyseal Union at Lower End of Radius and Ulna in the Age Group of 16-20 Years in Jodhpur Region of Rajasthan - Vaishnawa, Narendra Kumar; Jugtawat, J; Shrivastava, A; Vyas, P C (Journal of Indian Academy of Forensic Medicine, 2015)
Among the variety of scientific procedure available in age assessment, there is wide agreement in methods based on sexual, skeletal, and dental maturity. However in age group 16-20 years X-ray of lower end of radius and ulna is most accurate method. The present study was undertaken on 100 individuals from Jodhpur region (52 males and 48 female) between the age group of 16 to 20 years. Radiological examination of both wrist joints was done to study epiphyseal union at lower end of radius and ulna. The study showed that the processes of union start around 16 years in both male and female. Epiphyseal union at lower end of radius occurs in advance of the lower end of ulna and the difference is about one year. Average age for complete epiphyseal union of lower end of radius among the people of Jodhpur region is 17-18 year for both males and females. Average age for complete epiphyseal union of lower end of ulna among the people of Jodhpur region is for males 19-20 years and for females 18-19 years. The age for epiphyseal union of lower end of radius and ulna is bilaterally same.